On the triplet distribution and its effect on an improved phosphorescent organic light-emitting diode - Liu, S. W. (2013)
We reported phosphorescent organic light-emitting diodes with internal quantum efficiency near 100% with significantly reduced efficiency roll-off. It was found that the use of different hole transporting layer (HTL) affects the exciton distribution in the emission region significantly. Our best device reaches external quantum efficiency (EQE), current, and power efficiency of 22.8% ± 0.1%, 78.6 ± 0.2 cd/A, 85 ± 2 lm/W, respectively, with half current of 158.2 mA/cm2. This considerably outperforms the control device with N,N′-bis(naphthalen-1-yl)-N,N′-bis(phenyl)-benzidine (NPB) (HTL) and 4,4′-N,N′-dicarbazole-biphenyl (host) with maximum EQE, current and power efficiency of 19.1% ± 0.1%, 65.6 ± 0.3 cd/A, 67 ± 2 lm/W, respectively, with half current of only 8.1 mA/cm2.